Pengaruh Jarak Tanam Pada Pertumbuhan Dan Produksi Tanaman Pisang Di Lahan Terbuka - Silvia siska Halawa; Namyra Olivia Gulo; Darma Sah Tatema Laoli; Yakin Anugerah Laoli; Oscar Zemen Zebua; Yoel Melsaro Larosa (CV. SINAR HOWUHOWU, 2025)
This study aims to determine the effect of different planting distances on the growth and yield of banana plants in open fields. The research was conducted experimentally using a Randomized Complete Block Design (RCBD) with four spacing treatments: 2 x 2 m, 2.5 x 2.5 m, 3 x 3 m, and 3.5 x 3.5 m, each repeated four times. Observed parameters included plant height, number of leaves, stem diameter, number of bunches, bunch weight, and number of fruits per bunch. The results showed that planting distance significantly affected banana plant growth and yield. The 3 x 3 m spacing treatment produced the best vegetative growth and the highest yield compared to the other treatments. Therefore, a 3 x 3 m spacing is recommended for banana cultivation in open fields to achieve optimal results.